Pengaruh Electronic Word of Mouth Terhadap Keputusan Berkunjung Dimediasi oleh Destination Image: Studi pada Destinasi Wisata di Malang dan Yogyakarta - Siti Dyah Handayani; Misbahul Anwar; Insani Khoirudin; Achmad Sani Supriyanto (Institut Penelitian dan Pengembangan Mandalika (IP2MI), 2026)
The tourism industry is one of the sectors hardest hit by the COVID-19 pandemic. At the same time, this industry is a pillar of the Indonesian economy. Examining the tourism industry in research is therefore a pressing need at this time. Social media, as the primary source of information in this industry, plays a strategic role in shaping consumer behavior when determining which tourist destinations to visit. This study aims to analyze the impact of electronic word of mouth and destination image on visitation decisions at two tourist locations: Kampung Wisata Warna Warni Jodipan in Malang and Kampung Wisata Sayidan in Yogyakarta. These two locations were selected because these tourist villages are part of cultural tourism managed by the local community and serve as a source of income for the community, making them worthy of study. The study involved 150 respondents from the two locations and revealed that the three direct effects examined the influence of electronic word of mouth on destination image, and the combined influence of electronic word of mouth and destination image on visitation decisions were significant. However, the results differed regarding indirect effects, as destination image did not act as a mediator in the relationship between electronic word of mouth and visitation decisions